Development of Portable Pico Hydro Power Plant for Low Head Applications Using Cross-Flow Turbine - Budi Triyono; Dibyo Setiawan; Haryadi Haryadi; Vicky Wuwung; Zaki Odang; Norhafizan Ahmad (Politeknik Negeri Lhokseumawe, 2024)
The purpose of this research is to develop a portable Pico Hydro Power Plant (PHPP) using a cross-flow turbine type utilizing a head of less than 3 m with a target output electric power of 20 W which is sufficient for lighting or charging laptops and smartphones for activities in remote areas. Previous research has resulted in a prototype of a portable PHPP with a cross-flow type, but because the prototype construction was made using a 3D printing process; many obstacles were still encountered during manufacturing, installation, and testing. The development carried out in this study includes changes to the turbine housing, nozzle, outlet, bearing housing placement, and turbine runner. The resulting PHPP has advantages in simplicity in the manufacturing process, installation, and operation. Based on experiments or tests carried out at a head of 2.3 m, it shows that the electrical output power had met the output target of 20.5 W with a turbine efficiency of 39.6%.